Spontaneous reported cardiotoxicity induced by lopinavir/ritonavir in COVID-19. An alleged past-resolved problem. (1st February 2021) - Fresse, Audrey; Viard, Delphine; Romani, Serena; Gérard, Alexandre; Lepelley, Marion; Rocher, Fanny; Salem, Joe-Elie; Drici, Milou-Daniel
Abstract: The antiretroviral drug lopinavir/ritonavir has been recently repurposed for the treatment of COVID-19. Its empirical use has been associated with multiple cardiac adverse reactions pertaining to its ancillary multi-channel blocking properties, vaguely characterized until now. We aimed to characterize qualitatively the cardiotoxicity associated with lopinavir/ritonavir in the setting of COVID-19. Spontaneous notifications of cardiac adverse drug reactions reported to the national Pharmacovigilance Network were collected for 8 weeks since March 1st 2020. The Nice Regional Center of Pharmacovigilance, whose scope of expertise is drug-induced long QT syndrome, analyzed the cases, including the reassessment of all available ECGs. QTc ≥ 500 ms and delta QTc > 60 ms from baseline were deemed serious. Twenty-two cases presented with 28 cardiac adverse reactions associated with the empirical use of lopinavir/ritonavir in a hospital setting. Most adverse reactions reflected lopinavir/ritonavir potency to block voltage-gated potassium channels with 5 ventricular arrhythmias and 17 QTc prolongations. An average QTc augmentation of 97 ± 69 ms was reported. Twelve QTc prolongations were deemed serious. Other cases were likely related to lopinavir/ritonavir potency to block sodium channels: 1 case of bundle branch block and 5 recurrent bradycardias. The incidence of cardiac adverse reactions of lopinavir/ritonavir was estimated between 0.3% and 0.4%. These cardiac adverse drug reactions offer a new insight in its ancillary multi-channel blocking functions. Lopinavir/ritonavir cardiotoxicity may be of concern for its empirical use during the COVID-19 pandemic. Caution should be exerted relative to this risk where lopinavir/ritonavir summary of product characteristics should be implemented accordingly. Highlights: Lopinavir/ritonavir induces cardiotoxicity in COVID-19 Featured cardiac adverse events reflect ancillary multiple channel blocking properties Caution should prevail with off-label use because of its cardiotoxicity It summary of product characteristics must signal that risk